Industrial training report: Prudential Malaysia Assurance Berhad (PAMB). Special project: Demand for life insurance: a case study of Prudential Assurance Malaysia Berhad. / Anis Nabilah Azman - Azman, Anis Nabilah (Universiti Teknologi MARA, Perlis, 2021)
This report is being compiled as a requirement for student taking this course code of MGT 666, Industrial Training. As the format of this report is combining my industrial training experience with one agency under Prudential Assurance Malaysia Berhad (PAMB) and simple analysis related to the industry of the organisation. Next, this report has been prepared as a way to help the organisation improve matters that being a concern for their nature of business. The first part of this report starts with student’s profile represented by my resume as all basic information including education background, involvement and achievement are being provided. Next, the company’s profile part, there are more information regarding PAMB such as the background of company, logo, vision and mission, organizational structure, and products and services offered by their company. I briefly mentioned my industrial training experience on department I had been assigned, responsibility as an intern, assignment, and benefits received throughout this industrial training duration. On the next part which is analysis, there are many article found discussing on the same topic of ‘Demand for Life Insurance’ being obtained for literature review. As for methodology, the sample for this study is Malaysia and the data ranging from 2000 to 2020 with total 42 number of observations. The dependent variable is demand for life insurance and independent variables consist of inflation, economic growth, money supply and pandemic Covid-19. The regression result reveal that economic growth and money supply have a positive and significant relationship with life insurance while inflation and Covid-19 is insignificant in this study. Based on the result achieved, a discussion has been made regarding the relationship of two significant variables with dependent variable. Follows with recommendations for PAMB to take action according to the result suggested in the next part. Last but not least, I conclude my views about analysis being made for PAMB and also for my industrial training which include my vision and goals of myself in future.